Hasil Pemeriksaan Infeksi Menular Lewat Transfusi Darah (IMLTD) Menggunakan Metode CHLIA dan NAT di UDD PMI Kota Surabaya - Wiridania Ratna Puspita Dewi; Nia Lukita Ariani; Sri Mudayatiningsih (Jurnal Kesehatan Indonesia, 2026)
The transmission of Transfusion-Transmitted Infections (TTIs) such as HIV, Hepatitis B (HBV), Hepatitis C (HCV), and syphilis remains a major risk in the blood transfusion process. To minimize the risk of transmission during the window period, the Indonesian Red Cross Blood Transfusion Service (UDD PMI) utilizes the Chemiluminescence Immunoassay (CHLIA) and Nucleic Acid Testing (NAT) methods as screening tests. This study aimed to compare the results of IMLTD examinations using the CHLIA and NAT methods at the UDD PMI Kota Surabaya. This study employed a descriptive design conducted at the UDD PMI Kota Surabaya from January to August 2025. The sample consisted of 95 blood donor data selected using simple random sampling from secondary data obtained from the Blood Donor Management Information System (SIMDONDAR). Data were analyzed univariately and statistically tested using the Fisher Exact Test. The results of examinations using the CHLIA method showed that most samples were non-reactive, while a small proportion were reactive. Similarly, the NAT method indicated that the majority of samples were non-reactive, with only a few reactive results. There is no statistically significant difference between IMLTD examination results using the CHLIA and NAT methods at UDD PMI Kota Surabaya. The combined use of both methods is recommended to ensure optimal blood safety for transfusion recipients.